If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(-4) = 9x + 8 Reorder the terms for easier multiplication: -4f = 9x + 8 Reorder the terms: -4f = 8 + 9x Solving -4f = 8 + 9x Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by '-4'. f = -2 + -2.25x Simplifying f = -2 + -2.25x
| 9-(2y-3)=1-3y | | y-7=-1/2(x-4) | | (3x-9i)(x-3i)=0 | | 7(4y+5)=19y+8 | | 2y+y+9y= | | 15y=6y^2 | | a+1+a+3+2a=180 | | 1+3s=4 | | a+1+a+3+2a=90 | | x*y=31 | | 16f=1.8+32 | | c=2a+3 | | m/36=2 | | dxy=31 | | F(x)=-2x^2-5x+7 | | 7(x+5)+5=9x-2(x-4) | | 70=6p+34 | | 16=2a+5 | | 3x+5+6x-9=-4 | | -45=32 | | 4=-7s+53 | | 6b-3b=0 | | 50+d=2d | | 5x+x+20+40=180 | | x+y-12x+8y-8=0 | | 5x-64/9=64 | | 7(4y+5)=19+8 | | -u+2=220 | | w=x(y/z) | | N/0.6=8 | | 6=3a+3 | | 30-x=5x+6 |